2020
DOI: 10.21203/rs.2.14458/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Silencing of microRNA-210 inhibits the progression of liver cancer and Hepatitis B virus-associated liver cancer via targeting EGR3

Abstract: Background: This study was aimed to investigate the regulatory role of microRNA-210 (miRNA-210) on the progression of liver cancer and Hepatitis B virus (HBV)-associated liver cancer. Methods: The expression of miRNA-210 was detected in liver tissues of HBV-associated cirrhosis and liver cancer, and in HepG2 and HepG2.2.15 cells by qRT-PCR. MiRNA-210 was silenced in HepG2 and HepG2.2.15 cells by the transfection of miRNA-210 inhibitor. The cell viability and apoptosis was detected by MTT assay and Annexin V-fl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The results showed that miR-34a functions as a negative regulator of glucose metabolism and might be a novel marker for liver cancer prognosis. Li et al reported that mirRNA-210 silence exerted inhibition effect in the progression of liver cancer and hepatitis B virus-associated liver cancer via targeting EGR3 (7).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that miR-34a functions as a negative regulator of glucose metabolism and might be a novel marker for liver cancer prognosis. Li et al reported that mirRNA-210 silence exerted inhibition effect in the progression of liver cancer and hepatitis B virus-associated liver cancer via targeting EGR3 (7).…”
Section: Introductionmentioning
confidence: 99%
“…EGR3 was shown to be the target of miRNA-210, contrary to miRNA-210 the expression of EGR3 was downregulated in HBV-associated liver cirrhosis and liver cancer. In general, its role, like the role of miRNA-196a and miRNA-184, may be in proliferation promotion, and it is hard to assume whether the described mechanism with involvement in EGR3 regulation is specific for HBV-associated liver cancer, as far as EGR3 is known to be decreased in other cancers, like in head and neck cancers and gastric cancer [72]. miRNA-210 was also shown to be involved in bile acid-induced cholestatic liver injury through its direct target MLL4 (the histone methyltransferase mixed-lineage leukemia-4).…”
Section: Differential Expression Of Mirnas In Chronic Liver Diseasementioning
confidence: 99%
“…38 However, negative feedback of microRNA-210 silencing in the HepG2 and HepG2.2.15 cells for apoptosis promotion is likely to inhibit HCC progression. 39…”
Section: Virus -Hos T Epi G Ene Ti C Impac Tmentioning
confidence: 99%